Status of energy utilization and factors affecting rural households' adoption of biogas technology in north-western Ethiopia. Issue 3 (March 2021) - Marie, Mequannt; Yirga, Fikadu; Alemu, Getnet; Azadi, Hossein
Abstract: The National Biogas Policy of Ethiopia introduces plans for the implementation of biogas technologies in rural areas. However, rural households' decision to adopt biogas energy technology has been influenced by different socio-economic and institutional factors. This research was therefore undertaken to determine the actual energy consumption status and factors impacting the adoption of biogas technology by rural households in northwestern Ethiopia. Primary data from 182 randomly chosen households and 15 key informants were obtained. Different databases, such as journal articles, annual accounts, and unpublished papers, were used to gather secondary data. The data were analyzed using social science statistical package (SPSS 21st edition) tools using descriptive statistics, chi-square test, and independent-sample t-test. The results indicated that about 84.2% of the households have been using traditional biomass fuels (fuelwood, agricultural crop residue, dung cake, and charcoal) for baking Enjera and heating while the remaining 17.6% of the households have been using biogas energy. The kerosene lamp, battery cell, small size solar panel, and biogas were energy sources for lighting. The higher installation costs, inadequate water availability, shortage of cow dung, and lack of awareness were the main factors that hinder biogas installation in the study site. An independent sample t-test result revealed a statistically significant mean difference of the average time spent (in hours) to collect fuelwood per week between biogas technology adopters (M = 9.563, SD = 4.697) and non-adopters (M = 11.887, SD = 4.703; t (180) = 2.539, p = 0.012). In addition, findings of the binary logistic regression showed that education, access to markets, heads of cattle, and electronic media were the principal factors affecting biogas technology adoption significantly in the study area. Abstract : Adoption; Biogas technology; Binary logistic regression model; Biomass; Energy